A web-based remote radiation treatment planning system using the remote desktop function of a computer operating system: a preliminary report. - Suzuki K; Hirasawa Y; Yaegashi Y; Miyamoto H; Shirato H (Journal of Telemedicine & Telecare, 2009)
We developed a web-based, remote radiation treatment planning system which allowed staff at an affiliated hospital to obtain support from a fully staffed central institution. Network security was based on a firewall and a virtual private network (VPN). Client computers were installed at a cancer centre, at a university hospital and at a staff home. We remotely operated the treatment planning computer using the Remote Desktop function built in to the Windows operating system. Except for the initial setup of the VPN router, no special knowledge was needed to operate the remote radiation treatment planning system. There was a time lag that seemed to depend on the volume of data traffic on the Internet, but it did not affect smooth operation. The initial cost and running cost of the system were reasonable.